A Textbook on the History of Georgian Literature in Armenian - Lado Minashvili; Khatuna Gaprindashvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
The Armenian scholar, Professor Hrachik Bairamyan has for the first time compiled a textbook of Georgian literature of the 5th-19th centuries in Armenian. The book was published by Yerevan State University in 2007. The creation of a textbook, as noted by the author, was due to the demand of the times. The Armenian youth evinces considerable interest in the literature and culture of neighbouring Georgia. Hitherto there had not existed either an original or translated textbook. Hrachik Bairamyan’s book aims at filling this great gap. The author compactly acquaints us with the basic stages of development of Georgian literature, the life and works of all significant writers of the 5th-19th centuries. He has deemed it necessary to devote separate chapters to the major classics: Rustaveli, Ilia, Akaki, Vazha, dealing with the history of their translation into the Armenian language, their perception and evaluation by the Armenians, which should be considered a laudable novelty of the book. This book, written with good knowledge of the subject and love, will help Armenian youth to form an idea of the rich literature of the Georgian people, will predispose them with trust for the latter, will raise the Armenian interest in Georgian culture and serve as an impetus for an in-depth study of Georgian-Armenian literary and cultural relations.